Evaluation Of Transportation Performance Of City Transport in Tegal City - Rachmat Mudiyono; Nina Anindyawati; Ajie Setiawan (International Conference on Coastal and Delta Areas, 2017)
The problem of public transportation service in Tegal City is not yet optimal performance of urban transport service and border transportation caused by route of circular route so that public transportation service user will going in the opposite direction of difficulty obtaining public transportation. And not optimal network route performance caused by several route routes that overlap with other routes so that minimize Load Factor The proposed structuring of urban transport network and border in Tegal City 8 routes (2 urban transport routes and 6 border transport routes) to 14 routes consisting of 9 urban transport routes, namely A1, A2, A3, A4, A5, A6, A7, A8, A9 and 5 border routes, Tegal - Slawi, Tegal - Banjaran, Tegal - Pasar Bawang, Tegal - Kemantran and Tegal - Jatibarang . Keywords: public transportation, circular route, opposite direction, overlap